Core Java. Volume II. Advanced Features - Horstmann, Cay S. (USA : Pearson Education, 2022)
This volume focuses on the advanced topics that a programmer needs to know for professional software development and includes authoritative coverage of enterprise programming, networking, databases, security, modularization, internationalization, code processing, and native methods, as well as complete chapters on the Streams, XML, and Date and Time APIs. In addition, the chapter on Advanced Swing and Graphics covers techniques that are applicable to both client-side user interfaces and server-side generation of graphics and images.
Keywords: Advanced Features; Computer; Core; Java